A review of recent methodologies, technologies and usability in English language content delivery - Cheng L.K.; Selamat A.; Puteh F.; Mohamed F. (Penerbit UTM Press, 2023)
English Language Teaching (ELT) and content delivery have undergone vast shift in this era of modernization. With analogue content digitized as a common form of knowledge delivery, methodologies equipped with current technologies have produced new perspectives on English Language Learning. This paper reviews the status, context, teaching parameters, assessment parameters, teaching strategies and usability in the current research capacity of ELT, highlighting the current works with technologies in their content delivery methods. Emerging technologies in ELT has also inspires the other spectrum of study involving the usability of technological interfaces, which has evolved constantly with the progression of human and computer interactivity. The aim of this research is to rediscover usability evolution surrounding the technologies in ELT and to redefine the gap existed in between English learning and tools interactivity. Current technologies and usability measures used in ELT will be discussed, highlighting the current trends in gauging interface interaction. A summary of comparative results in the aforementioned works will also be highlighted in this review paper, together with the categorization of reviewed parameters, variables and metrics in ELT. The reviews conducted have shown that there are still many unexplored areas in ELT, ELT technologies and usability in ELT. 2016 Penerbit UTM Press. All rights reserved.